Análises de ações manipulativas em crianças da primeira infância praticantes de natação - Geamonond, Leonardo (Educación Física y Ciencia.)
The aim of this study was to evaluate the manipulative function of children from early childhood swimmers. The study included ten children swimmers of both gender in Uberlândia-MG. The selection was made randomly. The evaluation protocol of the aquatic motor development "Observation sheet of psychomotor aquatic Evolution" (by its acronym in Portuguese HOEPA) was used. This study found that 30.5% of students manipulated objects of different sizes and grabbed the edge of the pool, 20.5% of them found no problem in moving objects with their hands. The results of this research lead us to conclude that the aquatic psychomotor development in ball handling is deficient, so we must intervene early in the changes and stimulate normal development.